Automatic goals and conscious regulation in social cognitive affective neuroscience. Issue 2 (29th April 2014) - Sripada, Chandra; Swain, John D.; Ho, S. Shaun; Swain, James E.
Abstract The Selfish Goal model challenges traditional agentic models that place conscious systems at the helm of motivation. We highlight the need for ongoing supervision and intervention of automatic goals by higher-order conscious systems with examples from social cognitive affective neuroscience. We contend that interplay between automatic and supervisory systems is required for adaptive human behavior.